2024
DOI: 10.3390/pr12010140
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Antioxidant and Antibacterial Potential of Phenolic Extracts from Post-Distillation Solid Residues of Oregano, Rosemary, Sage, Lemon Balm, and Spearmint

Elisavet Bouloumpasi,
Magdalini Hatzikamari,
Stamatia Christaki
et al.

Abstract: Medicinal and aromatic plants (MAPs) are potential sources of natural polyphenols. Solid residues (SRs) from the essential oil (EO) industry are produced in significant volumes and may be used as natural sources of bioactive compounds. Therefore, this work was designed to examine the antioxidant and antibacterial characteristics of phenolic extracts obtained from SRs that have remained after EO distillation. SR extracts of Greek oregano, rosemary, spearmint, lemon balm, and Greek sage were assessed for their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Similarly, Bouloumpasi et al [6] reported that among five studied ethanolic extracts of post-distillation solid residues, lemon balm presented the highest antioxidant activity determined using ABTS, DPPH, and FRAP assays, followed by spearmint, Greek oregano, Greek sage, and rosemary, respectively.…”
Section: Comparative Performance Of Different Dess For Antioxidant Ex...mentioning
confidence: 86%
See 3 more Smart Citations
“…Similarly, Bouloumpasi et al [6] reported that among five studied ethanolic extracts of post-distillation solid residues, lemon balm presented the highest antioxidant activity determined using ABTS, DPPH, and FRAP assays, followed by spearmint, Greek oregano, Greek sage, and rosemary, respectively.…”
Section: Comparative Performance Of Different Dess For Antioxidant Ex...mentioning
confidence: 86%
“…The following regression Equations ( 4)- (6) The ANOVA results for the predicted response PCM are presented in Table 5. The ANOVA test revealed that the PCMs adequately represent responses of AC values for LB extracts.…”
Section: Data Availability Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, plants from the Lamiaceae, Apiaceae, and Asteraceae families can be easily found in the surrounding nature, making them accessible and economically viable for local communities as a source of traditional treatment for respiratory disorders. Lastly, Lamiaceae, Apiaceae, and Asteraceae are renowned for containing a variety of bioactive compounds (36), such as terpenoids, flavonoids, sesquiterpenes, and phenolic compounds, which are often associated with beneficial pharmacological properties for treating respiratory disorders. These compounds may have anti-inflammatory, antioxidant, expectorant, and antimicrobial effects, all of which are useful in addressing respiratory ailments (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%